2003
DOI: 10.1093/emboj/cdg295
|View full text |Cite
|
Sign up to set email alerts
|

The thyroid hormone receptor antagonizes CREB-mediated transcription

Abstract: Combinatorial regulation of transcription involves binding of transcription factors to DNA as well as protein±protein interactions between them. In this paper, we demonstrate the existence of a mutual transcriptional antagonism between the thyroid hormone receptor (TR) and the cyclic AMP response element binding protein (CREB), which involves a direct association of both transcription factors. TR inhibits transcriptional activity of CREB and represses activation of cAMP response element (CRE)-containing promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 61 publications
(82 reference statements)
7
57
2
Order By: Relevance
“…In agreement with this, we now show that ATF-2 transcriptional activity is markedly enhanced upon expression of Ha-ras val12 and is repressed by T3 in hepatocarcinoma cells. TRs can antagonize CREmediated transcription without binding to this motif by a direct interaction of the receptor with the b-Zip factor CREB (Mendez-Pertuz et al, 2003) and we now observe that the receptors can also interact with ATF-2. Whereas the liganded TRb1 represses cyclin D1 expression, it has been reported that repression via the CRE is lost in the TRb1 mutant PV (Furumoto et al, 2005).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In agreement with this, we now show that ATF-2 transcriptional activity is markedly enhanced upon expression of Ha-ras val12 and is repressed by T3 in hepatocarcinoma cells. TRs can antagonize CREmediated transcription without binding to this motif by a direct interaction of the receptor with the b-Zip factor CREB (Mendez-Pertuz et al, 2003) and we now observe that the receptors can also interact with ATF-2. Whereas the liganded TRb1 represses cyclin D1 expression, it has been reported that repression via the CRE is lost in the TRb1 mutant PV (Furumoto et al, 2005).…”
Section: Discussionsupporting
confidence: 56%
“…In agreement with this, mutation of CRE or Sp1 sites in the cyclin D1 promoter reduced induction by Ha-ras val12 and combined mutation of both motifs essentially abolished its effect (Figure 4a). TRs can interact with CREB inhibiting its phosphorylation (Mendez-Pertuz et al, 2003), and, as shown in Figure 4b, TRb1 also interacts directly with the b-Zip factor ATF-2 (activation transcription factor-2) in pulldown assays. In addition, cotransfection of a dominantnegative ATF-2 blocked the promoter response to Ha-ras val12 (Figure 4c), showing the implication of CRE-binding factors.…”
Section: Antagonism Of Ras Responses By Trb1mentioning
confidence: 95%
See 1 more Smart Citation
“…TR has been shown to bind other transcription factors and cofactors via its DBD (Poirier et al 2005, Matsushita et al 2007). An interesting interaction is the reported interaction of TR with cAMP response element binding protein (CREB), which is ensured via the DBD of TR (Mendez-Pertuz et al 2003, Furumoto et al 2005. Protein-protein interaction leads to an antagonism of CREB-mediated transcription by TR and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…TRs can also modulate expression of genes that do not contain a hormone response element by modulating the activity of other transcription factors and signaling pathways (2), including activator protein-1 (AP-1)-, cyclic AMP-response element-, and nuclear factor-B (NF-B)-dependent pathways (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%